2021
DOI: 10.1021/acscatal.0c04733
|View full text |Cite
|
Sign up to set email alerts
|

Engendering Unprecedented Activation of Oxygen Evolution via Rational Pinning of Ni Oxidation State in Prototypical Perovskite: Close Juxtaposition of Synthetic Approach and Theoretical Conception

Abstract: Rational optimization of OER activity of catalysts based on LaNiO3 oxide is achieved by maximizing the presence of trivalent Ni in the surface structure. DFT investigations of the LaNiO3 catalyst and surface structures related to it predict the improvement of OER activity for these materials to levels comparable with the top of the OER volcano if the La content is minimized while maintaining the oxidation state of Ni. These theoretically predicted structures of high intrinsic OER activity can be prepared by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 74 publications
(131 reference statements)
0
3
0
Order By: Relevance
“…As demonstrated in Figure S20, there is a minimal potential change after a continuous OER for 10 h. In addition, the OER electrocatalytic activity of the Ag/LNO- x electrocatalysts developed in this study is comparable to, or even higher than, that of the recently reported OER electrocatalysts based on perovskite and other metal oxide forms (Figure and Table S3). ,, Both Ag 0 and Ag + were detected by XPS before and after the OER, but the ratio of Ag + was slightly increased after the OER (Figure S21), indicating the slight oxidization of the Ag surface during the OER …”
Section: Resultsmentioning
confidence: 99%
“…As demonstrated in Figure S20, there is a minimal potential change after a continuous OER for 10 h. In addition, the OER electrocatalytic activity of the Ag/LNO- x electrocatalysts developed in this study is comparable to, or even higher than, that of the recently reported OER electrocatalysts based on perovskite and other metal oxide forms (Figure and Table S3). ,, Both Ag 0 and Ag + were detected by XPS before and after the OER, but the ratio of Ag + was slightly increased after the OER (Figure S21), indicating the slight oxidization of the Ag surface during the OER …”
Section: Resultsmentioning
confidence: 99%
“…[37][38][39][40] However, it can indirectly influence the valence state of B-site atoms, electronic conductivity, oxygen vacancies, and electrochemically active area in order to accomplish the goal of regulating the catalytic activity. [39,41,42] Based on this, researchers have investigated the modulation of A-site to increase the electrocatalytic performance of perovskite oxides for different applications. The general formula of (A 1-x A' x ) BO 3 /A 1-x BO 3 /A 1+x BO 3 is obtained by developing and…”
Section: Regulation Of A-sitementioning
confidence: 99%
“…During the electrocatalytic process, we usually consider that the A‐site metals are not participate in catalysis directly [37–40] . However, it can indirectly influence the valence state of B‐site atoms, electronic conductivity, oxygen vacancies, and electrochemically active area in order to accomplish the goal of regulating the catalytic activity [39,41,42] . Based on this, researchers have investigated the modulation of A‐site to increase the electrocatalytic performance of perovskite oxides for different applications.…”
Section: Regulation Of A‐sitementioning
confidence: 99%